The Physiology of Cold Weather Survival - Borg,A.; Veghte,J. H. (1973)
Contents: Thermogenetic mechanisms involved in man's fitness to resist cold exposure; Peripheral circulatory adjustment to cold; Introduction to winter survival; Methods in circulatory research; Local effects of acclimatization to cold in man; A physiological comparison of the protective value of nylon and wool clothing in a cold environment; Vibration injuries and cold exposure; Cold physiologic studies; Immersion hypothermia; Aircrew survival training in the United Kingdom and northern Norway; Snow avalanches. Presented at the AGARD Course on Cold Weather Survival, Spaetind High Mountain Hotel, Norway, 6-14 Apr 73. NATO furnished.